Not so Square nor so Round: Educational Trails and Sensitive Perceptions (Revista de Ensino em Artes, Moda e Design, 2025)
The act of drawing is an act of thinking, the content of which goes beyond rationality. This text is based on this premise, based on a historical document: the “Geometry Notebook” by the teacher Maria Altiva Costa, written in the late 1930s in Uberaba, Minas Gerais, Brazil. This study aims to explore the material and indicative condition of this document, considering it a place of appreciation and construction of a sensitive view of the world. Through it, we trace traces of the history of a religious school focusedon training teachers, in the context of the Escola Nova, the second phase of the modernist movement in Brazil, and the corresponding emphasis on doing, practicing and living together. The dialogue between the notebook and countless other sources was the theoretical-methodological procedure adopted in the research. The evidentiary process is concluded by proposing a different look at the old notebooks of a teaching considered formal and conservative.
Keywords: Drawing; Geometry; New school; Arts education